Resveratrol pretreatment reduces circulating inflammatory interleukins in CCl4-induced hepatotoxicity rats - Yasser I. Kandil; Anwar D. Maraqa; Ghaleb A. Oriquat; Ziad A. Shraideh (Faculty of Pharmacy, Cairo University, 2017)
Liver diseases represent one of major health burdens worldwide, both oxidative stress and inflammation play crucial roles in the development of liver diseases. Resveratrol (RSV), a naturally occurring compound, has recently been shown to exert anti-oxidative and anti-inflammatory actions. This work aimed to investigate the prophylactic effect of RSV against CCl4-induced hepatotoxicity in experimental rats in terms of inflammatory interleukins and histopathological changes. Twenty-four adult male rats were divided into three equal groups: group A: Negative control, received oral vehicle, group B: Positive control, received oral vehicle for 6â¯days and on 6th day injected with single dose of CCl4, and group C: RSV-treated group, received oral RSV (25â¯mg/kg/day) for 6â¯days and on 6th day injected with single dose of CCl4. 24â¯h after induction of hepatotoxicity by CCl4, all rats were sacrificed; liver was excised for histopathological studies and blood samples were collected. ALT, AST, ALP, total bilirubin, IL-1Î², IL-6, and IL-10 were determined in plasma while total GSH, MDA, GPx, and SOD were assayed in liver homogenate. Plasma levels of ALT, AST, ALP, total-bilirubin, IL-1Î², and IL-6 were significantly increased 24â¯h after induction of hepatotoxicity by CCl4 while IL-10 decreased. Pretreatment of rats with RSV prevented these changes. The histopathological changes were less obvious in livers of RSV-treated rats in comparative to positive control. In conclusion, RSV has a prophylactic effect against hepatotoxicity induced by CCl4 through decreasing the inflammatory interleukins level. Keywords: Resveratrol, Hepatotoxicity, Interleukins, Inflammation